Effect of graphene nano-platelet reinforcement on the mechanical properties of pressureless-sintered boron carbide. Issue 1 (January 2021) - Li, Z P; Gao, X J; Lin, G Q; Sun, S L; Li, K; Yang, S Y; Fang, S J; Zhang, W; Zhang, T; Wu, Y C
Abstract: Boron carbide (B4 C) doped with graphene nano-platelet (GNP) as reinforcement has been prepared by pressureless sintering. Effect of GNP addition on mechanical properties of the composite, such as fracture toughness, hardness, flexural strength was investigated. Phase evolution and microstructure was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results demonstrated that addition of GNP improved the fracture toughness (KIC) of B4 C with the decrease of hardness, flexural strength. The fracture toughness (KIC) can reach 4.45 MPam 1/2 with 1wt% addition of GNP, which was 49.3% higher than that of the composite without graphene platelets. It was found that the toughening mechanism can be contributed to pulling-out of graphene platelets, crack deflection, bridging and branching.